2008
DOI: 10.1590/s0021-75572008000100014
|View full text |Cite
|
Sign up to set email alerts
|

Apresentação das cardiopatias congênitas diagnosticadas ao nascimento: análise de 29.770 recém-nascidos

Abstract: Objective: To estimate the prevalence rate and study the clinical presentation and associated factors of congenital heart diseases diagnosed at birth between August 1990 and December 2003, at the Maternity Unit of the Hospital das Clínicas, Universidade Federal de Minas Gerais, Brazil. Methods:A retrospective, database driven study, part of the Latin-American collaborative study of congenital malformations. Records were reviewed on all live born (LB) and stillborn (SB) infants with congenital heart diseases di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 17 publications
(29 reference statements)
2
17
0
10
Order By: Relevance
“…The frequency of chromosomal abnormalities identified through karyotyping in our study (16.8%) was similar to that found in the studies of Ferencz et al 11 , Pradat 13 , Harris et al 19 and Amorim et al 20 , who found rates of 12.9-23.1%. Significant differences were observed in relation to the work of Stoll et al 12 , Hanna et al 14 , Goodship et al 15 , Grech and Gatt 3 , Meberg et al 16 , Roodpeyma et al 6 , Bosi et al 17 , Calzolari et al 18 Dadvand et al 21 and Hartman et al 22 , who found rates of 3-12.1% (p < 0.05).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The frequency of chromosomal abnormalities identified through karyotyping in our study (16.8%) was similar to that found in the studies of Ferencz et al 11 , Pradat 13 , Harris et al 19 and Amorim et al 20 , who found rates of 12.9-23.1%. Significant differences were observed in relation to the work of Stoll et al 12 , Hanna et al 14 , Goodship et al 15 , Grech and Gatt 3 , Meberg et al 16 , Roodpeyma et al 6 , Bosi et al 17 , Calzolari et al 18 Dadvand et al 21 and Hartman et al 22 , who found rates of 3-12.1% (p < 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Although our study was the only one that had the syndromic classification description made by a clinical geneticist, based only on the dysmorphologic physical examination findings of patients, our frequency of syndromic patients (29.5%) was similar to that reported by Calzolari et al 18 and Amorim et al 20 . Unlike ours, in these studies the patients were retrospectively divided into syndromic or not after the karyotype evaluation results and the presence of abnormalities in other organs.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations